Sense of Ethnic Belonging: Relation With Well-Being and Psychological Distress in Inhabitants of the Mapuche Conflict Area, Chile - García, Felipe E.; Villagrán, Loreto; Ahumada, María Constanza; Inzunza, Nadia; Schuffeneger, Katherine; Garabito, Sandra (Frontiers in Psychology, 2021)
Research has shown that experiences of discrimination cause harm to the health and well-being of people. In terms of the identity of members of a group, a positive evaluation of that group might involve devaluing the out-group as a way of raising the endo-group, causing discrimination toward the out-group. In the Chilean context, the Mapuche people have historically suffered discrimination and violations of their rights. The aim of this study was to assess the relationship between Collective Identity, perceived experiences of discrimination, psychological well-being and distress in the inhabitants of the Mapuche conflict zone according to their sense of belonging to their ethnic group (Mapuche, Mestizo, Caucasian). This descriptive, correlative, and cross-sectional study involved 200 participants, including 94 men (47%), and 106 women (53%), between the ages of 18 and 83 years old (M = 39.02; SD = 13.45), who had lived for at least 1 year in communities in the Araucanía Region. The sample was stratified according their sense of ethnic identity, including 30% Mapuche, 33.5% Caucasian, and 36.5% Mestizo. The results show that participants with a sense of Mapuche ethnicity experienced more instances of discrimination, had a greater sense of collective identity, and that they also supported the Mapuche social movement and its methods. Based on evidence that well-being is directly related to collective identity, the study undertook a regression analysis of emotional distress and the psychological well-being of participants. The interaction between experiences of discrimination and collective identity has a significant influence. Collective identity and experiences of discrimination in themselves as well as the interaction between them, predict psychological well-being. The results suggest that the importance of the Mapuche group’s identity phenomena are related to a broad socio-historical context that leads them to identify themselves as a collective in conditions of inequality. This relationship between well-being and collective identity could be explained by their sense of cultural belonging, which can be a factor in protecting mental health.